Design and Prototyping of a Dust Extraction System with a Suppression Mechanism: A Case Study of Limestone Dust on Small Scale Mines - Kambasu Bowen (Kabale University, 2023)
A lot of dust is generated during the course of various mine operations and also other economic activities most especially due to rock fragmentation. The dust is usually beyond the allowable concentrations hence causing negative effects to both human life and the environment. Wet suppression has been tried and currently in use but it interferes with the mine operations. This is why I came up with an idea for a dust collection system that cannot interfere with the mining operations and yet affordable. The dust collection system was designed to avoid the circulation of dust from the point source and the case study was the small scale limestone quarries located in kasese. The designed dust collection system comprises of the hood for capturing the dust from a point source, a cyclone for separating dust using centrifugal force, a hopper for breaking the vortex and an airtight container for collecting the dust. The machine was then tested to examine its efficiency and the efficiency was actually dependent on the length and diameter of the cyclone. Conclusions and recommendations were drawn from the discussed results got after testing. The designed machine had an efficiency of 78% total dust and replaceable filters will be recommended for further cleaning of the air. The major costs to be incurred by the system are the power costs. This designed system is the best to be used in all areas whether arid or not but only need availability of power.